Australian University Students’ Coping Strategies and Use of Pharmaceutical Stimulants as Cognitive Enhancers - Jensen, Charmaine; Forlini, Cynthia; Partridge, Brad; Hall, Wayne (Frontiers in Psychology, 2016)
Background: There are reports that some university students are using prescription stimulants for non-medical ‘pharmaceutical cognitive enhancement (PCE)’ to improve alertness, focus, memory, and mood in an attempt to manage the demands of study at university. Purported demand for PCEs in academic contexts have been based on incomplete understandings of student motivations, and often based on untested assumptions about the context within which stimulants are used. They may represent attempts to cope with biopsychosocial stressors in university life by offsetting students’ inadequate coping responses, which in turn may affect their cognitive performance. This study aimed to identify (a) what strategies students adopted to cope with the stress of university life and, (b) to assess whether students who have used stimulants for PCE exhibit particular stress or coping patterns. Methods: We interviewed 38 university students (with and without PCE experience) about their experience of managing student life, specifically their educational values, study habits and achievement, stress management, getting assistance, competing activities and responsibilities, health habits, and cognitive enhancement practices. All interview transcripts were coded into themes and analysed. Results: Our thematic analysis revealed that, generally, self-rated coping ability decreased as students’ self-rated stress level increased. Students used emotion- and problem-focused coping for the most part and adjustment-focused coping to a lesser extent. Avoidance, an emotion-focused coping strategy, was the most common, followed by problem-focused coping strategies, the use of cognition on enhancing substances, and planning and monitoring of workload. PCE users predominantly used avoidant emotion-focused coping strategies until they no longer mitigated the distress of approaching deadlines resulting in the use of prescription stimulants as a substance-based problem-focused coping strategy. Conclusion: Our study suggests that students who choose coping responses that do not moderate stress, where possible, may cause themselves additional distress and avoid learning more effective coping responses. Helping students to understand stress and coping, and develop realistic stress appraisal techniques, may assist students in general to maintain manageable distress levels and functioning. Furthermore, assisting students who may be inclined to use prescription stimulants for cognitive enhancement may reduce possible drug-related harms.